2017
DOI: 10.3791/55057
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Microvesicles from Peripheral Blood

Abstract: The release of extracellular vesicles (EVs) including small endosomal-derived exosomes (Exos, diameter < 100 nm) and large plasma membrane-derived microvesicles (MVs, diameter > 100 nm) is a fundamental cellular process that occurs in all living cells. These vesicles transport proteins, lipids and nucleic acids specific for their cell of origin and in vitro studies have highlighted their importance as mediators of intercellular communication. EVs have been successfully isolated from various body fluids and esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…“ Fig 1A ” shows the presence of CD9, CD63 and Hsp 70 proteins in exosomes isolated from the plasma of four healthy donors. We also analyzed the exosomes isolated by the above method for the presence of CD41 and CD45 antigens which are reported to be concentrated in microvesicles [ 9 ]. According to “ Fig 1B , detectable amounts of CD41 and CD45 antigens were not found in exosome pellet.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…“ Fig 1A ” shows the presence of CD9, CD63 and Hsp 70 proteins in exosomes isolated from the plasma of four healthy donors. We also analyzed the exosomes isolated by the above method for the presence of CD41 and CD45 antigens which are reported to be concentrated in microvesicles [ 9 ]. According to “ Fig 1B , detectable amounts of CD41 and CD45 antigens were not found in exosome pellet.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that when blood was drawn, there was very low concentrations of red cell-derived exosomes in blood but increase when blood is stored for longer periods of time. CD41 and CD45 proteins which originate from platelets and leucocytes, respectively are mainly present in microvesicles [ 9 ]. “ Fig 6C ” shows that CD41 and CD45 proteins are absent in exosomes isolated from stored blood samples indicating that exosomes isolated using Invitrogen kit was not contaminated with microvesicles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data revealed that MVs pelleted from EDTA-anticoagulated plasma samples by differential centrifugation were 100-600 nm in diameter. MVs can be distinguished from exosomes by detecting the presence of proteins tubulin, actinin-4, or mitofilin, while antibodies for CD9 and CD81 were used as markers for exosomes [85].…”
Section: Biomarkers On Microvesiclesmentioning
confidence: 99%